The Relationship Of Family Support And Elderly Activities In Posyandu With The Quality Of Life Of Elderly In The Working Area Of Pal Tiga Pontianak City Health Center - Fatya Rahmah; Yoga Pramana; Yuyun Tafwidhah (Journal of Innovative and Creativity, 2025)
Background: The rapidly growing elderly population faces multiple challenges affecting quality of life, including physical, cognitive, social, and mental decline. Family support and participation in Elderly Posyandu (Integrated Health Post) are considered important factors influencing elderly quality of life, yet their specific relationships in Indonesian urban settings remain underexplored. Objective: This study aimed to analyze the relationships between family support, elderly activity levels in Posyandu, and quality of life among elderly individuals in the working area of Puskesmas Pal Tiga, Pontianak City. Method: A correlational study with a cross-sectional design was conducted using a purposive sampling technique. The sample consisted of 84 elderly individuals aged 60 years and above registered at Posyandu Lansia Asoka. Data were collected using validated questionnaires measuring demographic characteristics, family support, and quality of life, along with attendance records. Data analysis employed the Spearman rank correlation test with a significance level set at p < 0.05. Results: Among respondents, 98.8% received good family support, 56% were active Posyandu participants, and 97.6% reported good quality of life. Statistical analysis revealed a significant positive relationship between family support and quality of life (r = 0.703, p = 0.000), but no significant relationship between elderly activity levels in Posyandu and quality of life (r = 0.019, p = 0.866). Conclusion: Family support significantly influences elderly quality of life, while Posyandu attendance frequency alone does not directly correlate with quality of life outcomes, suggesting the need for enhanced service quality and family-centered interventions.